Bendamustine in chronic lymphocytic leukemia: Outcome according to different clinical and biological prognostic factors in the everyday clinical practice. Issue 11 (9th September 2013) - Zaja, Francesco; Mian, Michael; Volpetti, Stefano; Visco, Carlo; Sissa, Cinzia; Nichele, Ilaria; Castelli, Monica; Ambrosetti, Achille; Puglisi, Simona; Fanin, Renato; Cortelazzo, Sergio; Pizzolo, Giovanni; et al.
<x xml:space="preserve">Abstract</x> Bendamustine proved to be effective for the treatment of chronic lymphocytic leukemia (CLL). However, the relationship between its activity with clinico‐biological prognosticators has been addressed only in few studies. We retrospectively evaluated the efficacy of bendamustine, in a real‐life contest, on 142 patients, median age 70 years, median number of previous regimens 2 (0–8, 13% previously untreated). Bendamustine was administered for a median number of 4 cycles, in 84% of cases with rituximab. Overall (ORR) and complete response (CRR) rates were 68 and 16.5%, respectively. Multivariate analysis demonstrated a relationship between ORR and number of prior treatments (OR 0.25, 95% CI 0.08–0.71; P = 0.009), del(17p) (OR 0.10, 95% CI 0.03–0.32; P < 0.001) and concomitant rituximab (OR 4.37, 95% CI 1.12–17.04; P = 0.033). The estimated 1‐ and 2‐years overall survival (OS) and progression free survival (PFS) rates were 76, 61, 51, and 26%, respectively. Previous sensitivity to fludarabine (HR 0.36, 95% CI 0.16–0.82), response to bendamustine (HR 0.21, 95% CI 0.10–0.45), and del(17p) (HR 2.18, 95% CI 1.002–4.74) had a prognostic significance in multivariate analysis for PFS, while the number of previous therapies (HR 3.48, 95% CI 1.29–9.38; P = 0.014), concomitant use of rituximab (HR 0.32, 95% CI 0.11–0.93) and response to bendamustine (HR 0.22, 95% CI 0.07–0.66) were significant for OS. Side effects included grade 3–4 neutropenia, infections, thrombocytopenia and anemia which occurred in 40, 14, 14, and 10% of patients, respectively. These results confirm the activity and safety of bendamustine and rituximab combination even in patients with unfavorable clinical and biological features excluding del(17p). Am. J. Heamtol. 88:955–960, 2013. © 2013 Wiley Periodicals, Inc.